Corporate dashboard for payphone service - Siraj, Fadzilah; Shadan, Hezlin (2015)
Making assured that managements are kept abreast of what is happening in the company is not an easy task.The quantity of data generated by the business process is astonishing large and non-centralized. The challenge facing business organizations is how to extract, load, transform data, and then deliver useful information to key decision makers.The major challenge for the payphone industries is in making a good decision, particularly to increase quality of service, customer satisfaction while achieving high revenue.With current practice, the process is very time consuming and therefore, a systematic and informative corporate dashboard needs to be provided especially for managerial level in supporting their decision making process.This paper proposed a dashboard application design that provides a single-screen display of relevant information such as the phone performance and coin collection reports, as well as generated revenue to enable faster and more effective decision making. The development of the dashboard is divided into requirement, design and implementation phases.The implementation using real data has demonstrated the potential use of the dashboard.The evaluation results indicate that the dashboard can be used as a tool that can support payphone operation works and decision process by providing the analytical analysis of the KPI report and the performance status.In addition, the results can be used as a guideline for the dashboard developer to understand the process and focuses on the key elements and the principle in designing the effective dashboard.